Study and Analysis of Almost Para Sasakian Type-Riemannian Manifold - Amar Nath; Manohar Singh Chahar (International Journal of Mathematics And its Applications, 2017)
In this paper, author studied and analyses Almost Para Sasakian Type-Riemannian manifold. The first section of this paper is introductory in nature, which deals with basic definition and literature review with previous known defined results. Second section deals with Almost Para Sasakian Type-Riemannian manifold (APST-Riemannian manifold) and its various applications and the third section is devoted for Para-K-contact type Riemannian manifold (PKCT-Riemannian manifold). As the outcomes of this work further detail theorems are suggested for future work.